The Smithsonian First Ladies Collection - Graddy, Lisa Kathleen (Smithsonian Books, 2014)
The Smithsonian First Ladies Collection features many treasures not on view at the exhibit. Complete with an insider's look at the acquisition, conservation, and exhibition of the pieces as well as a timeline of all forty-six first ladies, this is a must-have for anyone fascinated by these incredible women and their roles in American culture and political life.